Infant Feeding Practices in a Multi-Ethnic Asian Cohort: The GUSTO Study - Toh, Jia Ying (MDPI, 2016)
The optimal introduction of complementary foods provides infants with nutritionally balanced diets and establishes healthy eating habits. The documentation of infant feeding practices in multi-ethnic Asian populations is limited. In a Singapore cohort study (GUSTO), 842 mother-infant dyads were interviewed regarding their feeding practices when the infants were aged 9 and 12 months. In the first year, 20.5% of infants were given dietary supplements, while 5.7% took probiotics and 15.7% homeopathic preparations. At age 9 months, 45.8% of infants had seasonings added to their foods, increasing to 56.3% at 12 months. At age 12 months, 32.7% of infants were given blended food, although 92.3% had begun some form of self-feeding. Additionally, 87.4% of infants were fed milk via a bottle, while a third of them had food items added into their bottles. At both time points, more than a third of infants were provided sweetened drinks via the bottle. Infants of Indian ethnicity were more likely to be given dietary supplements, have oil and seasonings added to their foods and consumed sweetened drinks from the bottle (p < 0.001). These findings provide a better understanding of variations in infant feeding practices, so that healthcare professionals can offer more targeted and culturally-appropriate advice.